'It's not just all about the fancy words and the adults': Recommendations for practice from a qualitative interview study with children and young people with a parent with a life-limiting illness. (September 2022) - Marshall, Steve; Fearnley, Rachel; Bristowe, Katherine; Harding, Richard
Background: Healthcare professionals report challenges in supporting dying patients who have dependent children. These parents are often uncertain how to meet the needs of their children and require appropriate support from professionals. There is limited evidence based guidance for professionals around this issue, which is informed by the views and experiences of children themselves. Aim: To develop an understanding of the perspective of children on living with parental life-limiting illness and inform recommendations for healthcare professionals. Design: Qualitative semi-structured interviews were conducted, with thematic analysis of the data. Setting/participants: A diverse sample of 32 children aged 6–17, whose parent was living with life-limiting illness, were recruited from across the United Kingdom. Results: Despite the challenges of living with a parent with a life-limiting illness, the children display agency in their response. The children: feel a responsibility to look after their family; negotiate a relationship with healthcare; employ strategies to maintain some normality; and ensure that the inevitable sadness does not become overwhelming. Conclusions: Five recommendations for healthcare professionals were developed from the findings. Clinicians should encourage dying parents to: (1) acknowledge the agency of children; (2) recognise children's caregiving roles; (3) engender children's trust in healthcare; (4) maintain some normality; and (5) discuss emotions with their children. Implementing these recommendations will assist parents with a life-limiting illness to provide evidence-based support to their dependent children.